“A whole new world… wait, is it a whole, entire, or total world?” : the extraction of collocations for the three English synonym discrimination - Pariwat Imsa-Ard,; Supakorn Phoocharoensil, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study investigated three synonymous adjectives, ‘whole’, ‘entire’, and ‘total’, in terms of their collocations and strict sense of meaning. Data were drawn from three English dictionaries: 1) Oxford Advanced Learner's Dictionary (online version), 2) Merriam-Webster's Learner's Dictionary (online version), and 3) Longman Dictionary of Contemporary English (2014), and from the Corpus of Contemporary American English (COCA). The findings from this investigation revealed that the three adjectives share some common meanings, and they can thus be considered near synonyms. They may also be somehow interchangeable with each other in certain contexts, however, in terms of formality, the word ‘total’ is likely to be used the most in formal contexts. Concerning their common collocations, ‘whole’ and ‘entire’ share some noun collocates, some of which are associated with geographic vocabulary; namely America, Europe, and California. However, ‘entire’ and ‘total’ share only one strong noun collocate, which is population, while ‘whole’ and ‘total’ do not share any typical noun collocates. Significantly, corpus data can provide additional data which does not exist in dictionaries. The findings of this study may serve as supplementary materials for English language teachers to enhance students’ English vocabulary learning, especially when it comes to academic writing.